2005
DOI: 10.1097/01.rct.0000156396.13522.f2
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Imaging of Prostate Cancer

Abstract: The addition of DW imaging to conventional T2W imaging provides better detection of prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
132
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(146 citation statements)
references
References 19 publications
10
132
0
4
Order By: Relevance
“…Miao et al [16] showed that the sensitivity and specificity rates for T2WI was 76% and 70% respectively, compared with 86% and 80% for DWI. Combined T2WI and DWI yield slightly better results, with reported sensitivity and specificity rates of 45-89% and 61-97% respectively, compared with 74-85% and 57-95% respectively for DWI alone and 25-87% and 57-92% respectively for T2WI alone [12,15,[17][18][19][20][21][22][23][24][25][26].…”
Section: Potential Uses Of Dwi In Prostate Cancer Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Miao et al [16] showed that the sensitivity and specificity rates for T2WI was 76% and 70% respectively, compared with 86% and 80% for DWI. Combined T2WI and DWI yield slightly better results, with reported sensitivity and specificity rates of 45-89% and 61-97% respectively, compared with 74-85% and 57-95% respectively for DWI alone and 25-87% and 57-92% respectively for T2WI alone [12,15,[17][18][19][20][21][22][23][24][25][26].…”
Section: Potential Uses Of Dwi In Prostate Cancer Detectionmentioning
confidence: 99%
“…This may be attributed to increased contrast on DWI images compared with conventional imaging [46]. When combined with T2-weighted imaging, the sensitivity and specificity for PC range from 71 to 89% and 61 to 91% respectively, compared with 51-86% and 60-84% respectively for T2WI alone [17,19,21,22,47]. Lim et al [24] showed that combined T2WI and DWI imaging increased the AUC among readers from 0.66-0.79 for T2WI alone and 0.74-0.86 for DWI alone, to 0.76-0.9 (p<0.001).…”
Section: T2-weighted Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the reported results demonstrated low diagnostic sensitivity [115]. To increase the sensitivity of diagnosis, Shimofusa et al [34] suggested the addition of strong magnetic field gradient pulses (b-values) to the pulse sequence instead of using an endorectal coil. In their study [34], they detected the tumor in the central zone of the prostate in five of eight total patients using DWI with strong magnetic field gradient pulses.…”
Section: A Introductionmentioning
confidence: 99%
“…To increase the sensitivity of diagnosis, Shimofusa et al [34] suggested the addition of strong magnetic field gradient pulses (b-values) to the pulse sequence instead of using an endorectal coil. In their study [34], they detected the tumor in the central zone of the prostate in five of eight total patients using DWI with strong magnetic field gradient pulses. Alternatively, the compared diagnostic results with T 2 -weighted imaging, detected the tumor only in one of the eight patients.…”
Section: A Introductionmentioning
confidence: 99%